Priorities for the global advancement of care for older adults with cancer: an update of the International Society of Geriatric Oncology Priorities Initiative. Issue 1 (January 2021) - Extermann, Martine; Brain, Etienne; Canin, Beverly; Cherian, Meena Nathan; Cheung, Kwok-Leung; de Glas, Nienke; Devi, Beena; Hamaker, Marije; Kanesvaran, Ravindran; Karnakis, Theodora; Kenis, Cindy; Musolino, Najia; et al.
Summary: In 2011, the International Society of Geriatric Oncology (SIOG) published the SIOG 10 Priorities Initiative, which defined top priorities for the improvement of the care of older adults with cancer worldwide. 1 Substantial scientific, clinical, and educational progress has been made in line with these priorities and international health policy developments have occurred, such as the shift of emphasis by WHO from communicable to non-communicable diseases and the adoption by the UN of its Sustainable Development Goals 2030. Therefore, SIOG has updated its priority list. The present document addresses four priority domains: education, clinical practice, research, and strengthening collaborations and partnerships. In this Policy Review, we reflect on how these priorities would apply in different economic settings, namely in high-income countries versus low-income and middle-income countries. SIOG hopes that it will offer guidance for international and national endeavours to provide adequate universal health coverage for older adults with cancer, who represent a major and rapidly growing group in global epidemiology.